Too much is too little: Estimating the optimal physical activity level for a healthy mental state - Shimura, Akiyoshi; Masuya, Jiro; Yokoi, Katsunori; Morishita, Chihiro; Kikkawa, Masayuki; Nakajima, Kazuki; Chen, Chong; Nakagawa, Shin; Inoue, Takeshi (Frontiers in Psychology, 2023)
Introduction Although physical activity and exercise are generally thought to have favorable effects on mental health, excessive physical activity may have unfavorable effects. In this study, the associations between physical activity and the states of mental health with U-shaped dose–response curves were hypothesized, and the ranges of physical activity resulting in optimal effects on mental health were investigated. Methods A cross-sectional survey was conducted on 1,237 adult volunteers in 2017 and 2018. Of these volunteers, 526 participants validly answered the self-administered questionnaires asking about physical activity, depression, anxiety, resilience, insomnia vulnerability, and life events. A comparison of mental health measures by physical activity levels and quadratic equation model regressions were performed. Results No significant linear associations between physical activity levels and mental health measurements were observed; however, the U-shaped, quadratic equation models indicated a significance. The following levels of physical activity per week optimized the mental health measurements values of the participants: 6,953 MET-minutes and 25.70 h for depression, 5,277 MET-minutes and 21.60 h for state anxiety, 5,678 MET-minutes and 22.58 h for trait anxiety, 25.41 h for resilience, and 9,152 MET-minutes and 31.17 h for insomnia vulnerability. Conclusion Physical activities in the optimal range were associated with more favorable mental health measurements. Physical activities that were too much or too long and outside of the optimal range were associated with less favorable mental health measurements.